(untitled) (Czech Journal of International Relations, 1966)
Since its inception, Arab nationalism has been oppressed by nationalism generation and was known to be stimulated by external factors, while in Western countries Europe was mainly a manifestation of the growth of capitalist industrial relations, and thus the result of written internal processes. Nationalism in the Arab region of the front entrance took place primarily as a reaction against foreign domination (first Turkish, later British or French) and not just as an economic growth of the bourgeoisie. European colonial powers, although modern political and philosophical concepts that arose from the ravages of European science, although they made it possible for some partisans of the Arab countries to get to know them, however, chaic pre-capitalist industrial relations and thus Islam.